Evaluation of left ventricular regional myocardial function by layer-specific strain in female patients with hypothyroidism - Ding, Xiao; Zhang, Xijun; Wei, Changhua; Yuan, Jianjun; Shen, Kaikai; Wang, Yisa; Zhu, Haohui (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to explore the value of layer-specific strain in evaluating the differences in left ventricular 18-segment myocardial function between female hypothyroidism patients and healthy controls.MethodsThirty-two female hypothyroidism patients (hypothyroidism group, HG) with normal left ventricular global systolic function and 30 healthy female volunteers (control group, CG) underwent two-dimensional echocardiography. Offline analysis using EchoPAC113 software measured peak systolic circumferential strain (PCS) and peak systolic longitudinal strain (PLS). Layer-specific strain values (endocardium, mid-myocardium, epicardium) were compared between groups.ResultsPLS of the endocardium (PLS-endo) of the posterior wall in the middle segments of the left ventricle in HG was lower than that in CG. PCS of the mid-myocardium (PCS-mid) and epicardium (PCS-epi) of all walls in the apical segments of the left ventricle in HG were lower than those in CG. In the middle segments of the left ventricle in HG, the PCS-epi of the anterior septum, PCS-mid and PCS-epi of the anterior wall, PCS-mid and PCS-epi of the inferior wall, and PCS-endo, PCS-mid, and PCS-epi of the lateral and posterior walls were lower than those in CG. In the basal segments of the left ventricle in HG, the PCS-mid and PCS-epi of the anterior wall, PCS-mid and PCS-epi of the posterior wall, PCS-epi of the inferior wall, and PCS-endo, PCS-mid, and PCS-epi of the lateral wall were lower than those in CG. The global circumferential strain (GCS) of the mid-myocardium and epicardium in the basal and apical segments, as well as all layers in the middle segment, was significantly lower in HG.ConclusionsThe layer-specific strain values in the left ventricle in female patients with hypothyroidism differed from those of healthy female controls. When evaluating the left ventricular regional myocardial function in female patients with hypothyroidism, circumferential strain was, to a certain extent, more affected by thyroid hormone abnormalities than longitudinal strain.